Basic Architecture and Applications of DNA Computing - Nordiana, Rajaee; Azham, Zulkharnain; Awang Ahmad Sallehin, Awang Husaini (Transactions on Science and Technology, 2016)
DNA computing is a new computing paradigm utilizing actual DNA oligonucleotides to do computation by employing biomolecular tools to get the reaction and outputs extraction. In this paper, we introduce basic architecture of DNA computing. Brief explanation on the biomolecular tools employed in DNA computing are also included, and its various applications in many fields are also discussed.